Aproximación a la didáctica de traducción publicitaria francés/castellano - Juan Manuel Ibeas-Altamira; Lydia Vázquez (Ikastorratza.e-Revista de Didáctica, 2019)
Teaching, translation and advertising: three worlds not always being neatly linked which have a lot to say. This study does a brief exploration of advertising translation studies, and their place in a global world. Without focusing the teaching practices upon the teacher's lectures, but trying to allow the learner to manage the process, with some examples extracted from the Medias and the net. Our work puts forward a didactic proposal for French-Spanish advertising translation in which encouragement of the student autonomy play an essential role.